Evaluation of metal contamination in soil samples around thermal power plant in Turkey - Turhan, Şeref; Altıkulaç, Aydan (Author(s), 2018)
Thermal power plants lead to major environmental problems such as the generation of acid gases and fly ash. Heavy metals contained in fly ash have potential risks for human health and soil and water ecosystems. Therefore, it is of great importance to study the heavy metal contamination of soil around the coal-fired thermal power plants. In this study, the concentrations of Cr, Ni and Hg in surface soil samples from the area around the Kangal lignite-fired thermal power plant (LFTPP) were analysed by using energy dispersive X-ray fluorescence (EDXRF) spectrometry to assess the contamination level of soils. The average metal concentration of Cr, Ni and Hg was found as 713.2 ppm, 610.1 ppm and 1.7 ppm. Each soil sample contamination with Cr, Ni and Hg was estimated using ecological parameters such as the enrichment factor (E-F), contamination index (C-F) and Nemerow integrated pollution index (I-PL). The average value of E-F and C-F estimated for Cr, Ni and Hg were found as 1.8, 2.2 and 4.3, 8.6, 10.5, 20.7, respectively. The results indicate that the soils around Kangal LBPP were moderate polluted to very strongly polluted with Cr, Ni and Hg. The I-PL values varied from 9.2 to 119.3 with an average value of 17.7. The evaluation result of I-PL revealed that the soil samples were very high polluted.

34th International Physics Congress of the Turkish-Physical-Society (TPS) - SEP 05-09, 2018 - Konacik, TURKEY

WOS: 000468358900056

Turkish Phys Soc
Keywords: Metal Contamination; Thermal power plant; 13. Climate action; 7. Clean energy; 6. Clean water